Financial Inclusion Model on the Development of Batik SMEs in Cirebon Regency - Hamzah, Amir; Suhendar, Dadang (Jurnal Minds: Manajemen Ide dan Inspirasi, 2020)
This study aims to analyze the financial inclusion model on Batik SMEs' development in Cirebon Regency. Six constructs emerge as the objects of interest are financial literacy, financial technology, social capital, capital structure decisions, financial inclusion, and business development. 176 Batik-Cirebon artisans fill the questionnaires under the non-probability sampling technique and are analyzed using CB-SEM. The results prove that financial literacy, financial technology, social capital, capital structure decisions have a positive effect on financial inclusion, and financial inclusion positively affects business development Batik SMEs In Cirebon Regency.